Teaching and Learning Pronunciation: EFL Learners’ Views and Instructors’ Practices - Gazan, Mehmet; Gürbüz, Nurdan (E- Kafkas eğitim araştırmaları dergisi (Online), 2025)
The discussion surrounding the significance of pronunciation in communication, both in a first language (L1) and a second language (L2), has been a subject of ongoing debate. Previous research has predominantly focused on exploring teachers' techniques and practices regarding pronunciation instruction, as well as investigating students' opinions and perceptions. This study seeks to enhance our understanding of pronunciation instruction within an English as a Foreign Language (EFL) context by offering insights into both learners’ views and instructors’ practices jointly. Conducted as a mixed-method study, the research investigated the perspectives of both students (n = 112) and instructors (n = 14) on the learning and teaching of pronunciation. The findings revealed that learners placed considerable importance on pronunciation instruction and expressed a preference for audio-visual materials, repetition, and imitation techniques respectively. On the contrary, the majority of instructors, who reported including pronunciation in their teaching, emphasized the effectiveness of focusing on the phonetic alphabet the most, while considering textbook-based activities to be the least effective component of their instructional repertoire. These findings may contribute to a better understanding of the teaching and learning of pronunciation in an EFL context and could help inform future instructional strategies and educational practices.